Designing a Digital Branding Pattern in Healthy Agricultural Products - Abolghasem Mohammadnezhad Ali Zamini; Arezo Ahmadi danyali; Mahmoud Ahmadi Sharif (ارزش آفرینی در مدیریت کسب و کار)
Abstract The aim of this research is the digital branding model of healthy agricultural products. The research method is applicable in terms of its purpose, and exploratory in terms of its descriptive and analytical nature. The qualitative research method was carried out using the data-based method and Max QDA software, and the code collection tool was a semi-structured interview in the form of a purposive sampling method, and theoretical saturation was achieved with 13 experts in this field. Also, with 82 open coding, 22 central and selective categories, the model of digital branding of healthy agricultural products in Iran was designed. Digital branding of healthy agricultural products is centered around the creation of brand meaning and brand power, which initiates under influence of casual conditions, and makes sense with different strategy of digital brand creation and brand power, and strengthens the brand culture in the target community by compiling and implementing a combination of brand-aligned marketing and integrated communication marketing, and visualizes the identity and personality of the digital brand of healthy agricultural products in the mind of the customer. The strategy under the influence of intervening factors is trying to fulfill the demand for food safety and health, and gains fame by fulfilling the promise of the brand and delivering a healthy product at a reasonable price, and repeated purchase of agricultural products by loyal customers requires more production and causes employment and rural economic prosperity. Extended Abstract Introduction Agriculture has existed since ancient times, and continues to be a vital area of ​​human activity today (Bahcecik et al., 2019). It also is the only source of food, an important supplier of raw materials for industry, as well as a significant market for production (Adamov et al., 2016). Agricultural trade plays an important role in the implementation of national goals and strategic goals of the country. Effectiveness, efficiency of labor productivity and support of employment, small and medium businesses and support of individual entrepreneurship, international cooperation and export have been established due to agricultural businesses. This issue, which is one of the most important and promising parts of the domestic economy, provides not only the food security of the country but also the social welfare of the people. In addition, agriculture plays a major role in shaping the country's export capacity and import substitution program. In recent years, agricultural trade has been developed in most industries in raw materials and feed production.  This has been facilitated by sanctions and the growing demand for safe and quality food products (Butova et al., 2019). The country of Iran is proficient in the production of agricultural products, and produces all kinds of agricultural and garden products every year; all Iranian products have a high capacity to be branded due to Iran's special climatic conditions and the country's four season, but unfortunately, many products that are at a high level in terms of quality are bought in bulk and exported to other countries and sold under the brand of these companies; therefore, the lack of a suitable brand is one of the weaknesses of Iran's agriculture, which demands that this sector be given a proper arrangement. Producers of healthy agricultural products should understand the potential of the Internet as a branding tool in the agricultural sector because the Internet can be a powerful branding tool for healthy agricultural products beyond labels and brochures. The use of the main components of Internet marketing, such as e-mail, online stores, websites, social networks, viral marketing and content increases the contact points with actual and potential customers and shortens the distance between the product supply and the consumer market, and enables receiving feedback from the brand community. In this research, an attempt has been made to answer the question: what is the pattern of digital branding of healthy agricultural products in Iran? Theoretical Framework The pressure to compete with other brands and differentiate with others creates motivation and creates the need for branding. Today, due to factors such as the increase of actors entering a sector, the changing demand of buyers and the increasing expectations of export markets; small business units are forced to review traditional business practices. In a competitive situation, the success of a product largely depends on the perception of its target audience. Branding can be critical to a company's long-term success, especially for companies that operate in markets with many clusters of buyers and sellers and few differentiated products (Ghafourian Shagerdi et al., 2019). Sharma et al., (2023)  in examining the adoption of digital branding among specialty dining startups in a post-pandemic environment concluded that digital branding plays an important role as an independent branding strategy and increases the performance of specialty dining startups in the post-pandemic era. In addition, it highlighted the significant mediating effect of digital support and awareness on digital brand adoption intention. Amidabad et al., (2023) in an article titled Designing a digital marketing model in the brand of online business companies, using a qualitative mixed approach. In the qualitative part of the research, the researcher-made fuzzy Delphi questionnaire was used. The experts were selected through purposive and non-probability sampling, and in-depth and semi-structured interviews were conducted with them. In the quantitative part of the research, the fuzzy Delphi technique was used to screen the obtained indicators, then the interpretive structural modeling method was used to identify the causal relationships between the main research articles. Overall, the model obtained consists of 5 main categories, including digital marketing strategy, personalization, content marketing, interaction with consumers, and mixed digital marketing. Based on the results, it was shown that the digital marketing strategy is the most basic element of the model and is an external independent variable. This variable has an effect on content marketing, interaction with consumers, and mixed digital marketing. Marin & Nilă (2021) in a research titled Branding in the social network: the use of the LinkedIn network in personal brand communication, investigated the attitude of recruitment and human resources professionals towards the development of a personal brand in LinkedIn and the criteria used in the evaluation of a communication and marketing specialist. Quantitative research based on two questionnaires was used to understand the perceptions of the study participants. The results showed that social media networks are a useful tool for developing a personal brand, but communication and marketing professionals show moderate involvement. Similarly, recruitment professionals have high expectations while communication and marketing professionals use similar methods to present themselves. Shafiee et al., (2016) in a research entitled presenting a local branding model for online retail sales using the qualitative method of data-based theory, used theoretical sampling by using the qualitative method and conducting semi-structured interviews with knowledgeable people and experts in the field. After conducting interviews and collecting information, the codes obtained in different sections were analyzed, and after performing the three steps of open, central, and selective coding, the final model was obtained; which includes the sum of central categories, causal conditions, intervening conditions, strategies, and finally, the consequences and results of branding. The results of the research show that the authentic brand prevents the effort to recognize other competitors. online payment through secure banking intermediaries increases trust in the digital brand. Methodology This research is designed based on the approach of basic constructivist theory, which is suitable for understanding the complex, problematic, and relativist nature. Data was collected through semi-structured interview on a sample. Marketing managers and digital branding experts and consultants were purposefully selected based on theoretical sampling criteria. Theoretical sampling means that participants are selected based on emergent analysis; and the theory that is created from the data is subsequently modified from the data obtained from subsequent participants. A total of 13 experts have been interviewed, and theoretical saturation was achieved with this number. Max QDA version 2020 software was used for qualitative analysis and coding of semi-structured interview data. Discussion and Results In this research, for the analysis of indicators and findings in the qualitative part, the data-based theory including three stages of coding was used. In the first stage, primary codes and concepts were extracted using the key points of the interviews. Then 22 main categories and 82 subcategories were extracted. The indicators were analyzed in 3 stages of open, axial, and selective coding. Max QDA 2020 software was used for data analysis, and a total of 113 codes were extracted from 13 interviews in the form of 22 main categories and 82 subcategories. According to the indicators obtained in the research process and the analyzes performed on them, the final model was obtained using the coding method. Conclusion Digital branding of healthy agricultural products is centered around the creation of brand meaning and brand power, which initiates under influence of casual conditions, and makes sense with different strategy of digital brand creation and brand power, and strengthens the brand culture in the target community and visualizes the identity and personality of the digital brand of healthy agricultural products in the mind of the customer. The strategy under the influence of intervening factors is trying to fulfill the demand for food safety and health, and gains fame by fulfilling the promise of the brand and delivering a healthy product at a reasonable price, and repeated purchase of agricultural products by loyal customers requires more production and causes employment and rural economic prosperity.